Impact of Mobile Medical Units on Anaemia Prevalence and Treatment Adherence in Rural India - Banoj Kumar Mahanta; Narayan Rao Sameni; Sudeep Sinha; Puspita Datta (Rajiv Gandhi University of Health Sciences, 2024)
Background Anaemia poses a significant health challenge in rural India particularly among women. Limited access to healthcare services exacerbates this issue. Mobile Medical Units MMUs have been introduced to address this gap by providing essential healthcare services to underserved populations. Objective This study investigates the effectiveness of MMUs in reducing anaemia prevalence and improving treatment adherence among women in rural areas of Uttar Pradesh and Jharkhand. Methodology A mixed-methods approach was employed combining quantitative surveys and qualitative interviews. The study surveyed 399 women across four districts Ranchi and Khunti in Jharkhand and Prayagraj and Bahraich in Uttar Pradesh. Data on anaemia prevalence treatment adherence and barriers to accessing MMU services were collected and analyzed. Results The findings revealed a high prevalence of anaemia 88 among the surveyed women with moderate-to-severe anaemia constituting 45. MMUs significantly contributed to treatment adherence with 96 of women following medical advice. However 13.5 of participants received no medication indicating gaps in service delivery. The study also identified barriers such as lack of awareness and inconvenient timing of MMU visits. Conclusion MMUs play a crucial role in addressing anaemia in rural India by improving treatment adherence and reducing anaemia prevalence. However gaps in service delivery and barriers to access need to be addressed. Recommendations include strengthening community engagement improving awareness campaigns and promoting dietary diversification to enhance the effectiveness of MMU interventions.